Instrumentos de detecção do uso de álcool em homens idosos: Um estudo populacional na região metropolitana de São Paulo, Brasil - De Oliveira, Janaina Barbosa; Santos, Jair Lício Ferreira; Kerr-Corrêa, Florence [UNESP]; Simão, Maria Odete [UNESP]; Lima, Maria Cristina Pereira [UNESP] (My University, 2011)
Objective: This study compares the efficacy of the AUDIT (gold standard) with the more easily and quickly applied instruments CAGE, TWEAK, and T-ACE for men aged ≥ 60 using data from a representative stratified sample of the general population of metropolitan São Paulo.Method: The GENACIS questionnaire was administered to a total sample of 2,083 people aged over 18, with a response rate of 74.5%.The elderly male sample consisted of 169 men. Sensitivity, specificity,positive and negative predictive values, area under the receiver operating characteristic curve, and confidence intervals were calculated for each instrument (95% CI). Results: Respondents were predominantly married (81.7%), had up to 11 years of education (61.3%) and a monthly per capita income of up to 300 US dollars. Current abstinence rate was high (61.6%) and 38% reported being former drinkers. There were no statistically significant differences among the instruments tested; however, the TWEAK had a higher area under the receiver operating characteristic curve (95% CI; 0.90-0.99). Conclusion: Research in the general population with screening instruments is scarce, especially among the elderly. However, it can provide specific information concerning this age group and be useful in the formulation of policies and prevention strategies.
Alcohol screening instruments in elderly male: A population-based survey in metropolitan São Paulo, Brazil
Keywords: Alcoholism; Epidemiology; Geriatric psychiatry; Men; Psychometrics